1994
DOI: 10.1021/tx00037a011
|View full text |Cite
|
Sign up to set email alerts
|

Structure-genotoxicity relationships of allylbenzenes and propenylbenzenes: A quantum chemical study

Abstract: Quantum mechanical calculations at the semiempirical level (AM1 method) were conducted for estragole (1), methyleugenol (2), safrole (3), alpha-asarone (4), beta-asarone (5), elemicin (6), allylbenzene (7), eugenol (8), trans-anethole (9), isosafrole (10), and myristicin (11), and the results compared with the known genotoxicity of 1-6 and the absence of genotoxicity of 7-11 (unscheduled DNA synthesis assay). The various compounds showed no significant differences in the relative stability of the radical speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 16 publications
0
16
1
1
Order By: Relevance
“…An example of the failure of the PNR model was recendy published by Testa and coworkers (44). These workers found that the genotoxicity of allylbenzenes and propenylbenzenes did not correlate with the PNR derived enthalpy of activation.…”
Section: When the Pnr Model Will Failmentioning
confidence: 99%
“…An example of the failure of the PNR model was recendy published by Testa and coworkers (44). These workers found that the genotoxicity of allylbenzenes and propenylbenzenes did not correlate with the PNR derived enthalpy of activation.…”
Section: When the Pnr Model Will Failmentioning
confidence: 99%
“…As with allyl alcoholic substituents, propargyl alcoholic substituents (CsC-C-OH) that contain at least one hydrogen on the alcoholic carbon are also known to undergo enzymatic oxidation to the corresponding a,6-unsaturated carbonyl metabolites and are quite toxic (46)(47)(48). In addition, propargyl alcohols that contain an aromatic substituent on the alcoholic carbon may undergo Phase-n sulfate conjugation reactions to yield electrophilic species analogous to 10 (49). It is advisable that chemists either avoid propargyl alcoholic moieties altogether during the design of a chemical substance or, if this moiety is necessary, incorporate the same structural modifications described above for allyl alcoholic moieties to prevent or reduce bioactivation to electrophilic metabolites.…”
Section: -Alkyl-phenols: Bioactivation To P-quinone Methidesmentioning
confidence: 99%
“…In terms of chemical constituents, plant-based volatile oils can be categorized as terpenoids and phenylpropanoids that contain phenylpropenes, which are the major components of various essential oils. Phenylpropenes can be chemically classified as propenylbenzenes (e.g., anethole), which have a 1,2-double bond and are non-genotoxic, and allylbenzenes (e.g., safrole), which have a 2,3-double bond and are carcinogenic according to rodent studies [8]. Although the latter are nonreactive, their metabolites (allylbenzenes-2,3-oxide) develop toxicity when they undergo cytochrome P450-metiated 1-hydroylation followed by sulfation.…”
Section: Introductionmentioning
confidence: 99%